1991
DOI: 10.1007/bf01369803
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of diazepam levels in bone marrow versus serum, saliva and brain tissue

Abstract: The distribution of diazepam in biological fluids and tissues of rats was examined 1, 2, 4 and 8 h after intraperitoneal administration by using a radioimmunoassay with specific anti-diazepam antibody. The diazepam levels in serum, saliva, brain and bone marrow decreased over a period of 2 h and levelled off 4 h after administration. The diazepam concentration in bone marrow was much higher than in serum, saliva and brain, suggesting an accumulation of diazepam in this tissue. This indicates that bone marrow c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…Winek et al [15] demonstrated that, in rabbits, peak ethchlorvynol blood level occurs 10-30 min after intraperitoneal injection and peak BM level between 15 and 60 min. In rats, diazepam clearance appears to be slower in BM than in blood, resulting in higher and longer BM impregnation [64]. This phenomenon was also reported in rats by Watterson et al for diazepam [29] and fentanyl [26]: they assumed that accumulation occurred in BM and then in bone, followed by slow redistribution from bone to blood via BM.…”
Section: Correlation Between Bm and Blood Concentrationsmentioning
confidence: 79%
See 2 more Smart Citations
“…Winek et al [15] demonstrated that, in rabbits, peak ethchlorvynol blood level occurs 10-30 min after intraperitoneal injection and peak BM level between 15 and 60 min. In rats, diazepam clearance appears to be slower in BM than in blood, resulting in higher and longer BM impregnation [64]. This phenomenon was also reported in rats by Watterson et al for diazepam [29] and fentanyl [26]: they assumed that accumulation occurred in BM and then in bone, followed by slow redistribution from bone to blood via BM.…”
Section: Correlation Between Bm and Blood Concentrationsmentioning
confidence: 79%
“…fatty and cellular proportion) in different bones according to age, sampling location was claimed by Winek et al [15] and McIntyre et al [2] to be a relevant factor that should be investigated. Likewise, hydrophilic or lipophilic behavior of molecules should be considered: Winek et al showed that blood/BM correlation of water soluble compound, such as methanol [23], ethanol [17], isopropanol and acetone [18], was improved correcting their concentration for water content, whereas other authors described accumulation in BM of lipophilic drugs like diazepam [2,29,64].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Therefore, the main analyte in saliva is predominantly the parent drug [55,65] and drug concentrations might be dependent on the pH value in this body fluid. The relationship between the saliva/plasma drug concentration ratio, pKa, pH and binding is expressed by the equations of Rasmussen/Matin [45].…”
Section: Biological Data On Drug Monitoring In Salivamentioning
confidence: 99%
“…Although methods have been described for one or two benzodiazepines (sometimes the major metabolite), it seems that no screening procedure has been reported for such pharmacologically-active drugs in oral fluid. Data are available for diazepam [3,4], clobazam [5], nitrazepam [6], flunitrazepam [7], zolpidem [8] and lorazepam [9]. Because of their extensive protein binding (95-99%), benzodiazepines are only present in oral fluid in very small concentra- tions, about some ng/mL.…”
Section: Introductionmentioning
confidence: 98%